Experimental behavior of novel GFRP reinforcing bars under compressive loads - Almerich-Chulia Ana; Martin-Concepcion Pedro; Molines-Cano Jose M; Moreno-Puchalt Jesica (Magazine of Civil Engineering, 2023)
Glass fiber-reinforced polymer (GFRP) bars have been used in RC structures due to their high tensile strength capacity and resistance to corrosion in comparison with steel. However, international standards do not recommend their use in RC structure elements subjected to compressive loads. Currently, there is no standard method to determine the compressive characteristics of FRP bars. This article presents a new type of GFRP bars designed specially to support compressive loads: they have additional winding GFRP layers around the longitudinal fibers. An exhaustive experimental study was carried out to obtain compressive properties of the bars: compressive strength, Young’s modulus and stress-strain relation. After post-processing the experimental results of the study, this paper showed compressive strength between 50% and 60% of tensile strength, which allows employing the bars as internal reinforcement in RC structures. Their obtained Young’s modulus is the same in both tensile and compression, which enables the linear stress-strain relation to be extended to the entire range of deformations. This is most advantageous for structural analysis procedures in the linear elastic regime. Finally, based on the experimental results of failure modes, some limitations about the cross-sectional area or the slenderness were proposed for the use as internal reinforcing in RC structures, which helps the researchers in the design procedure for members reinforced with FRP bars.